PEMANFAATAN GOOGLE MAP API GUNA OPTIMALISASI IDENTIFIKASI ASET PEMERINTAH KOTA SEMARANG DENGAN METODE PASSING MULTIPLE PARAMETERS - Endang Lestariningsih; eka ardhianto; W. T. Handoko; Edy Supriyanto (Jurnal Informatika Upgris, 2018)
The Law on Regional Autonomy has the impact of the Regional Government having the authority to manage the assets and regional income independently. Semarang City is an area in the Central Java Province managed by the local government of Semarang city that is required to be able to carry out autonomy well. One of the things done is the management of land and building assets owned by Semarang city government that functioned for the public interest and the implementation of city government semarang. data of government assets owned by Semarang city government recorded in Identity Card belonging to the Regional Finance and Asset Management Agency (DPKAD) there are 3,092 plots of asset managed by Regional Secretariat, Institution under Semarang City Government and management by sub-district and kelurahan area.Land assets managed by the municipal government of Semarang are currently not considered optimal. The application of the management information system for the location of the city government's land assets is planned to use the Google Maps Application Programming Interface (API), can be viewed as a solution to help the implementing officer recognize the location of the asset land and provide competitive advantages and advantages in an effort to transparency of the city government semarang on assets owned and the achievement of Semarang city to semarang be smart city.With the support of management information system application of land asset location of Semarang city government which can represent referring to location of location of real asset with remote sensing (sensing) is expected to be used effectively to manage, control and control the land asset.